First determination of DNA virus and some additional bacteria from Melophagus ovinus (sheep ked) in Tibet, China - Liu, Yong-Hong; Ma, Yi-Min; Tian, Hong-Ou; Yang, Bo; Han, Wen-Xiong; Zhao, Wei-Hong; Chai, Hai-Liang; Zhang, Zhan-Sheng; Wang, Li-Feng; Chen, Lei; Xing, Yu; Ding, Yu-Lin; et al. (Frontiers in Microbiology, 2022)
Melophagus ovinus (sheep ked) is one of the common ectoparasites in sheep. In addition to causing direct damage to the host through biting and sucking blood, sheep ked is a potential vector of helminths, protozoa, bacteria, and viruses. Sheep M. ovinus samples from three regions in Tibet were selected for DNA extraction. The 16S rDNA V3-V4 hypervariable region was amplified, after genomic DNA fragmentation, Illumina Hiseq libraries were constructed. The 16S rRNA sequencing and viral metagenomics sequencing were separately conducted on the Illumina Novaseq 6000 platform and molecular biology software and platforms were employed to analyze the sequencing data. Illumina PE250 sequencing results demonstrated that the dominant bacteria phylum in M. ovinus from Tibet, China was Proteobacteria, where 29 bacteria genera were annotated. The dominant bacterial genera were Bartonella, Wolbachia, and Arsenophonus; Bartonella chomelii, Wolbachia spp., and Arsenophonus spp. were the dominant bacterial species in M. ovinus from Tibet, China. We also detected Kluyvera intermedia, Corynebacterium maris DSM 45190, Planomicrobium okeanokoites, and Rhodococcus erythropolis, of which the relative abundance of Kluyvera intermedia was high. Illumina Hiseq sequencing results demonstrated that 4 virus orders were detected in M. ovinus from Tibet, China, and 3 samples were annotated into 29 families, 30 families, and 28 families of viruses, respectively. Virus families related to vertebrates and insects mainly included Mimiviridae, Marseilleviridae, Poxviridae, Ascoviridae, Iridoviridae, Baculoviridae, Hytrosaviridae, Nudiviridae, Polydnaviridae, Adomaviridae, Asfarviridae, Hepeviridae, Herpesviridae, and Retroviridae; at the species level, the relative abundance of Tupanvirus_soda_lake, Klosneuvirus_KNV1, and Indivirus_ILV1 was higher. African swine fever virus and many poxviruses from the family Poxviridae were detected, albeit their relative abundance was low. The dominant bacterial phylum of M. ovinus from Tibet, China was Proteobacteria, and the dominant bacterial genera were Bartonella, Wolbachia, and Arsenophonus, where 23 out of 29 annotated bacteria genera were first reported in M. ovinus. Kluyvera intermedia, Corynebacterium maris DSM 45190, Planomicrobium okeanokoites, and Rhodococcus erythropolis were detected for the first time. All DNA viruses detected in this study have been reported in M. ovinus for the first time.